CREATION OF THE REBI INSTRUMENT AS AN INSTRUMENT FOR THE FUTURE - Anusirwan, Anusirwan (International Journal of Social Science, 2025)
This article focuses on the creation and development of Rebi as the process of modernizing traditional musical instruments. The research is titled The Creation of the Rebi Instrument as the Instrument of the Future. Rebi is a development of a traditional instrument similar to the rebab, which is an advancement of the Rabab Pariaman (West Sumatra). This study aims to address the issues identified by the researcher and provide information to the public about the necessity of developing traditional instruments to make them more modern and relevant. The creation of a new musical instrument is considered crucial for the sustainability of traditional music across Indonesia, especially in West Sumatra, as evidence of the dynamism of traditional music. The object of this study is the Rabab Pariaman, a traditional Minangkabau instrument that is played with a bow and is at risk of extinction. Therefore, it is essential to develop the instrument to ensure its continued value. Data collection techniques used in this research include field observation, interviews, documentation, and literature studies. The research method used is a descriptive-analytic approach with a qualitative methodology, analyzing and describing the findings from the field in writing. This study also elaborates on the process of creating Rebi based on the research findings, which are then linked to the fields of organology and acoustics, resulting in a new musical instrument with a distinctive tone color. The creation of this new instrument is deemed vital for the preservation of traditional music in Indonesia, particularly in West Sumatra, and serves as proof of the dynamism and innovation within traditional music